2015
DOI: 10.1186/s40902-015-0002-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect on bone formation of the autogenous tooth graft in the treatment of peri-implant vertical bone defects in the minipigs

Abstract: BackgroundThe aim of this study was to evaluate the effect of autogenous tooth bone as a graft material for regeneration of bone in vertical bony defects of the minipigs.Material and MethodsSix minipigs were used in this study. Four molars were extracted in the right mandibular dentition and sent to the Korea Tooth Bank for fabrication of autogenous tooth bone. Ten days later, each extraction site was implanted with MS Implant Narrow Ridge 3.0x10mm fixture (Osstem, Seoul, Korea) after standardized 2mm-sized ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
0
9
0
1
Order By: Relevance
“…[ 3 ] Various in vivo and animal studies have demonstrated its biocompatibility, osteoinductive, and osteoconductive potential. [ 21 22 23 24 25 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] Various in vivo and animal studies have demonstrated its biocompatibility, osteoinductive, and osteoconductive potential. [ 21 22 23 24 25 ]…”
Section: Discussionmentioning
confidence: 99%
“…In this technical report, the ABTB acted as a scaffold for the implant, which penetrates the thin sinus floor to the apex of the ABTB. This method is known as the "ring technique," which was developed based on reports from animal studies and human clinical trials 10 11 . In 2014, the author was the first to report the technique and short-term clinical results of ABTB with simultaneous sinus implant.…”
Section: Discussionmentioning
confidence: 99%
“…Araştırmacılar, otojen diş kemik greftleri ile defekt çevresinde yeni kemik oluşumunun sağlandığını ve kemik-implant yüzey bağlantısının kontrol grubuna göre yüksek olduğunu bildirmişlerdir. 73 Lee ve arkadaşları, 74 sinüs ogmentasyonunda kemik doku oluşumunda ODKG'nin etkisini incelemişlerdir. 18-24 aylık 5 adet küçük domuzun kullanıldığı çalışmada, sağ maksiller sinüs ODKG ve sol maksiller sinüs sentetik kemik grefti ile ogmente edilmiştir.…”
Section: Hayvan çAlışmalarıunclassified